RESTATEMENT OF PT GARUDA INDONESIA’S FINANCIAL STATEMENTS IS CONSERVATIVE? - Yuni Pristiwati Noer Widianingsih; Nikke Yusnita Mahardini; Tulus Prijanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research is a case study research at PT Garuda Indonesia Tbk (PT GIAA). The motivation for conducting the research was the existence of PT GIAA's fi-nancial reporting in 2018 which revealed a significant increase in profit which required PT GIAA to restate its financial statements in 2019. The analysis used was descriptive and quantitative analysis. The restatement of the financial state-ments has an impact on changes in reported earnings, namely there are losses, adjustments to accounts also cause some changes in the amounts recognized in the financial statements. On this basis, a quantitative analysis was carried out to determine the level of conservatism in the restatement of PT GIAA's financial statements. Based on accrual conservatism, the company still applies conserva-tism principles but in the restatement period of financial reporting in 2018 the level of conservatism decreased. Based on market conservatism, the market value of the company's shares is lower than its book value, this indicates that the company is aggressive in determining book value. Even the average stock return each year is negative and a sharp decline occurred during the restatement of fi-nancial statements. This indicates that market confidence decreases when the company restatement its financial statements.